Artemisia annua L. Aqueous Extract Promotes Intestine Immunity and Antioxidant Function in Broilers - Guo, Shiwei; Ma, Jiaxin; Xing, Yuanyuan; Shi, Lulu; Zhang, Linghui; Xu, Yuanqing; Jin, Xiao; Yan, Sumei; Shi, Binlin (Frontiers in Veterinary Science, 2022)
This study was conducted to investigate the effects of Artemisia annua L. aqueous extract (AAE) on intestinal immune and antioxidative function of broilers. A total of 200 one-day-old Arbor Acre broilers were randomly allotted into five dietary treatment groups, with five replicates per treatment and eight broilers per replicate. The five treatment diets were formulated by adding, respectively, 0 (control group), 0.5, 1.0, 1.5, and 2.0 g/kg AAE in the basal diet. The results showed that dietary inclusion of AAE quadratically decreased interleukin (IL)-1β content, linearly decreased IL-6 content in the small intestine through regulating the nuclear factor-kappa B signal pathway, and quadratically increased immunoglobulin (Ig)M and sIgA content in ileum and jejunum. Besides, there was a quadratic decrease in the gene expression of IL-1β, IL-6, and toll like receptor 4 (TLR4) in ileum on day 21, and the gene expression of IL-6 and TLR4 in duodenum on day 42, thereby improving small intestinal immune function in broilers. Additionally, dietary inclusion of AAE improves antioxidative function through the nuclear factor-erythroid 2-related factor 2 (Nrf2) signal pathway in the small intestinal mucosa of broilers, especially, quadratically increased catalase (CAT) and superoxidase dismutase activity in ileum, and total antioxidant capacity and glutathione peroxidase activity in duodenum, and quadratically decreased malondialdehyde concentration in ileum, besides, linearly increased heme oxygenase-1 and Nrf2 gene expression in jejunum and ileum on day 42, quadratically increased CAT gene expression in the small intestine. Furthermore, regression analyses of the above parameters showed that the optimal dose range of AAE in the diet of broilers was 1.12–1.38 g/kg.